ELECTROSPRAY IONIZATION MASS SPECTROMETRY FRAGMENTATION PATHWAYS OF SALTS OF SOME 1,2,4-TRIAZOLYLTHIOACETATE ACIDS, THE ACTIVE PHARMACEUTICAL INGREDIENTS - Borys, Varynskyi; Andriy, Kaplaushenko; Vladymyr, Parchenko (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The goal of this research was to study fragmentation pathways of series salts of 1,2,4-triazolylthioacetate acids. Methods: The study was done in the Electrospray ionization source with single quadrupole mass spectrometer Agilent 6120 after elution through column Zorbax SB-C18, 30 mm Ã— 4.6 mm, 1.8 Î¼m at Agilent 1260 infinity high-performance liquid chromatography system. The series salts of 1,2,4-triazolylthioacetate acids were studied. These salts are active pharmaceutical ingredients of potential or registered pharmaceutical formulations. Results: The mass spectra of corresponding compounds have analyzed. The fragmentation patterns of these compounds decay have proposed. Conclusions: Studying the fragmentation of the indicated substances can be used for detecting the mentioned substances, as well as for confirming the structure of new compounds with the mass spectrum based on the patterns described above.